Efektivitas Pijat I Love You (ILU) Dalam Mengatasi Gangguan Konstipasi Pada Bayi Usia 6-12 Bulan - Aotari, Wanti (Jurnal Keperawatan Muhammadiyah, 2025)
Background : Constipation is a digestive disorder that causes difficulty and pain during bowel movements with a frequency of bowel movements less than 3 times a week. One of the intervention methods that can be used in addition to pharmacological methods is the I Love You (ILU) massage method, where this method is starting to be widely used to overcome constipation in infants. This study aims to determine the effectiveness of I Love You (ILU) massage in overcoming constipation in infants aged 6-12 months. Methods : The method in this study is a quasi experiment with a non-equivalent control group design. The sample in this study were 40 infants aged 6-12 months who were divided into 2 groups, namely 20 infants in the I Love You Massage intervention group and 20 infants who were not given ILU Massage. Result : Data analysis using the Mann Whitney test with the P-Value results, namely 0.000 <0.05. It can be concluded that there is a difference in the frequency of infant defecation between the group that underwent I Love You Massage and the group that did not undergo ILU Massage. Conclusion : The ILU Massage method is a safe non-pharmacological intervention to treat constipation in infants and supports broader knowledge in clinical practice to improve infant health and well-being